2020
DOI: 10.1111/ejss.12954
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plastic mulch and nitrogen fertilizer on the soil microbial community, enzymatic activity and yield performance in a dryland maize cropping system

Abstract: Farming practices that integrate plastic film mulching and nitrogen (N) fertilization have been extensively used to enhance crop productivity. However, the interactive effects of mulching and N application on soil microbial properties and crop yields have received little attention. A 2‐year field experiment was carried out in the Loess Plateau to investigate the independent and combined effects of plastic mulch and N application rate on the soil microbial population, enzymatic activity and grain yield. From 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 49 publications
(65 reference statements)
5
36
0
1
Order By: Relevance
“…Some earlier studies described that the exogenous application of selenium at lower levels can improve the antioxidant activity and the tolerance of plants [31]. Similar results of some other researches also describe that low Se doses can enhance the antioxidant activities whereas higher Se causes a reduction [15,50].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Some earlier studies described that the exogenous application of selenium at lower levels can improve the antioxidant activity and the tolerance of plants [31]. Similar results of some other researches also describe that low Se doses can enhance the antioxidant activities whereas higher Se causes a reduction [15,50].…”
Section: Discussionsupporting
confidence: 58%
“…Maize (Zea mays L.) is considered an important crop worldwide [15,16]. e annual yield of maize in Pakistan is about 3.13 million tons [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Sustainable greenhouse tomato production requires optimal fertilizer management to achieve the double-win strategy of producing high yields and maximizing profits with less environmental impacts. 6 Optimal and scientific fertilization can not only provide essential nutrients for plant growth, 7 but also increase nutrients availability. 8 Extensive studies have shown that, compared with organic cropping systems, conventional farming increased yield of pakchoi and Chinese cabbage, 9 and had higher soil nitrogen fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal and scientific fertilization can not only provide essential nutrients for plant growth, 7 but also increase nutrients availability 8 . Extensive studies have shown that, compared with organic cropping systems, conventional farming increased yield of pakchoi and Chinese cabbage, 9 and had higher soil nitrogen fertility 10 .…”
Section: Introductionmentioning
confidence: 99%